Pengembangan Kampung Baratan Boyolali Sebagai Pusat Edukasi Permaculture Dan Ekowisata Agraris - Sidiq, Afif Taftayani; , Dr. Ir. Qomarun, MM; , Ir. Samsudin Raidi, MSc (2016)
Shifting diet and lifestyle of today's modern man , impact on public health . Various chronic diseases arise from wrong food habits . The trend of fast foods and processed products instantly, plus a sedentary lifestyle , or less active , triggering metabolic system disorders , which in turn increases the risk of chronic disease. Permaculture has become one of the main topics in the field of sustainable issues agrarian country . Permaculture is believed to be the most holistic approach in planning and designing sustainable . In the context of livehood sustainability , permaculture approach is an important alternative engaged in efforts to produce organic food crops , home design , layout of the village, and a healthy environment , a way to produce energy , and the development of a sustainable economy . Baratan villages is an area with land use and livestock farming activities , and the development of settlement activity . The village is surrounded by rice fields and the majority of the villagers are farmers . According to data obtained from Jeron villages , rice fields dikelurahan Jeron is divided into two immortal rice and industrial areas . While paddy rice fields kampong westerlies is eternal . Until now, development has been carried out is still not optimal. xix From this final project planning process has several problems, that is: How does the concept of developing and designing the development of Kampung westerlies Boyolali As Permaculture Education Center and Ecotourism Agriculture capable of supporting community activities include training, learning and production in the agriculture sector ? Thus the authors had the initiative to develop a village that will serve as a center of education and ecotourism permaculture agriculture. Where there are children farming and permaculture , gardening children , omah compost , agricultural training and research center , bamboo and organic market garden , Omah Livestock , Lumbung Padi , Omah Tani , Workshop Center and so on. The village is expected to add knowledge to villagers about sustainable agriculture and food security independently . Besides being used as a village Kampung educational tours that focus on agriculture and permaculture.